Leadership, Existence of Social Support, Organizational Commitment, and Work Satisfaction That Influence Turnover Intention In Health Industry - Yessica Rebecca Tambunan (Universitas Syiah Kuala, 2023)
High employee turnover rates in the healthcare industry can disrupt the internal functioning of organizations. The type of organizational leadership, the existence of social support, employee satisfaction and organizational commitment are interrelated and affect turnover. This study aims to complement existing knowledge by exploring the influence of organizational leadership style, the existence of social support, organizational commitment and work satisfaction that influence turnover intention in the health industry companies. This research was conducted by involving 170 employees working in hospitals across Jabodetabek (Jakarta-Bogor-Depok-Tangerang-Bekasi). Data analysis was performed using Structural Knowledge Creation (SEM) PLS. The results of this study proves that transformational leadership has a positive effect on employee satisfaction, but has a significant negative effect on turnover intention. Psychopathic leadership has a positive effect on turnover but does not have a negative effect on employee satisfaction. Social support has a positive effect on employee satisfaction but does not have a negative effect on turnover intention. Employee satisfaction has a positive effect on organizational commitment but does not have a negative effect on turnover intention. Organizational commitment has no negative effect on turnover intention. The managerial implications in this study that can be applied in organizations are attention to the leaders’ attitude in the organization, and create a pleasant work atmosphere by building social support in the work environment will be able to increase employee satisfaction and influence their commitment to the organization